Composition of the mother’s milk I. Protein contents, amino acid composition, biological value (Review) - Salamon, Szidónia; Csapó, János (Acta Agraria Kaposváriensis, 2008)
The authors have analysed protein contents, protein fractions, free amino acid and total amino acid contents of the mother’s colostrum and mother’s milk in comparison with the newest publications. They have established that there was no united picture of the different effects on protein contents of the mother’s milk. Protein contents of the colostrum of well-nourished mothers were found 6.0%, whereas those of underfed ones 4.5%. Some argue that there is a significant positive relationship between protein contents of food and daily protein intake, as well as protein contents of the mother’s milk. Some researchers were found the protein contents of the underfed mothers’ milk to be lower, while others found no difference in true protein contents of the milk of underfed and appropriately fed mothers (0.8âˆ’1.0%), and more could not evidence a difference in mothers of different nationality. Completed the mother’s nutriment with protein, in a part of the experiments protein contents of the mother’s milk increased, whereas others have reported reducing protein contents when completing with protein. Concerning the protein fractions, casein contents of the colostrum were measured to be 3.8 on average; while those of the mature milk 5.7 g/l; which values were for the Î²- casein 2.6 and 4.4 g/l, and for the Îº-casein 1.2 and 1.3 g/l. Î±-lactalbumin contents were found to be 3.62 and 3.26 g/l; lactoferrin contents 3.5 and 1.9; serumalbumin contents 0.39 and 0.41; immunoglobulin A contents 2.0 and 1.0; immunoglobulin M 0.12 and 0.20; and immunoglobulin G 0.34 and 0.05 g/l in the colostrum and the mature milk, respectively. NPN contents of the mother’s milk were measured to be significantly higher (25% in total protein %) than those of the cow’s milk (5%), with main component being the carbamide and free amino acids. It has been established that the total free amino acid provide only 2% of the requirements of a newborn baby, in nutritional respect it is an important fraction as it is easily utilizable for the synthesis of the nerve tissue and the neurotransmitters. Free amino acids are very important for the afterbirth development; especially taurine, serine, glutamic acid and glutamine, which give a considerable portion of the total free amino acids. Taurine was found to be essential for the development of the newborn, as taurine production from cysteinesulfonic acid is rather restricted due the limited activity of the cysteinesulfonic acid decarboxylase enzyme. Taurine takes part in the conjugation of the bilious acids and has a significants role in the formation of the retinal receptors. Serine has an important role in the casein synthesis, as well as it is a precursor of neuroactive substances, and a component of the biosynthesis of phospholipids. High concentration of glutamic acid in the milk can be useful, as glutamic acid has a key position in the amino acid metabolism, and converted into Î±-ketoglutaric acid it can enter the tricarboxylic acid cycle. By analysis the amino acid composition of the mother’s milk protein it was established that around 20% of it is glutamic acid, whereas it contains in the smallest amount histidine, cysteine and methionine. Proportion of the essential amino acids is around 42%, which abundantly cover the requirements of the newborns. Some have established a relation between essential amino acid contents of the milk protein and the essential amino acid contents of the food, while others deny the existence of such a relation. Cysteine/methionine ratio of the mother’s milk is higher than that of cow’s milk, the amount of phenylalanine and tyrosine is lower, due to the higher proportion of the whey proteins.
Keywords: mother’s milk; colostrum; protein contents; protein fractions; free amino acids; amino acid composition; biological value